'Unexpected' spelling difficulty in a 10-year-old child with good reading skills: An intervention case study. Issue 2 (2nd July 2016) - Roncoli, Silvia; Masterson, Jackie
ABSTRACT: We report a single-case intervention study of Alan, a child aged 10;04, who presented with spelling difficulty but good reading skills. Assessment of the potential cognitive functions underlying the spelling difficulty explored phonological abilities, visual memory and letter report. We also assessed print exposure and verbal memory. Results of analysis of spelling performance revealed an effect of word length on accuracy, and spelling errors involving omission, insertion, substitution and transposition of graphemes. Results of the literacy-related assessments indicated that Alan did not have a phonological or visual memory deficit, but he showed impaired performance in the letter-report task when asked to report all the letters in the five-item test array. On the basis of previous research, we hypothesised that Alan's unexpectedly poor spelling was due to a graphemic buffer deficit. Two different interventions were employed: a lexical-orthographic programme, followed by one aimed at improving sublexical abilities. The results showed a significant increase in spelling accuracy after the lexical-orthographic intervention for the treated word set, and a small improvement for the untrained words that was significant at delayed post-intervention testing. The improvement was shown to persist over time. No improvement in spelling was observed after the sublexical intervention. The study emphasises the importance of a wide assessment in order to investigate cognitive processes underpinning spelling difficulty.